Pengaruh Kemampuan Kerja dan Kompensasi terhadap Produktivitas Kerja dengan Disiplin Kerja sebagai variabel intervening pada Guru di Phatnawitya School Yala Thailand - Sari, Vanny Wulan; Harini, Sri; Sudarijati, Sudarijati (Universitas Batanghari Jambi, 2025)
This study aims to identify the direct and indirect effects of job skills and compensation on teacher productivity through work discipline at Phatnawitya School, Yala, Thailand. Employing a quantitative approach with descriptive and verificative methods, data collection involved primary and secondary sources through literature review and field studies. Path analysis was utilized, with a sample of 65 teachers selected via saturation sampling. Findings indicate that job skills directly influence work discipline, while compensation directly impacts work discipline. Job skills also directly affect teacher productivity, as does compensation. Additionally, work discipline directly affects teacher productivity and mediates the relationship between job skills, compensation, and teacher productivity.